Common anticholinergic solanaceaous plants of temperate Europe - A review of intoxications from the literature (1966–2018). (15th April 2020) - Fatur, Karsten; Kreft, Samo
Abstract: Datura stramonium, Atropa belladonna, Hyoscyamus niger, and Scopolia carniolica are all temperate plants from the family Solanaceae, which as a result of their anticholinergic tropane alkaloids, hyoscyamine/atropine and scopolamine, have caused many cases of poisoning around the world. Despite the danger these nightshade plants represent, the literature often presents incomplete cases lacking in details and filled with ambiguity, and reviews on the topic tend to be limited in scope. Many also point to a gap in knowledge of these plants among physicians. To address this, the following review focuses on intoxications involving these plants as reported in the literature between 1966 and 2018, with brief mention to pertinent related plants to contextualise and provide a fuller picture of the situation surrounding the presently discussed temperate plants. Analysis of the literature displays that D. stramonium is largely associated with drug use among teens while A. belladonna is primarily ingested as a result of the berries being mistaken for edible fruits. H. niger was found to be largely ingested when mistaken for other plants, and S. carniolica was the cause of incredibly few intoxications.